NO DEEP POCKETS: SOME STYLIZED EMPIRICAL RESULTS ON FIRMS’ FINANCIAL CONSTRAINTS - Carreira, Carlos (2010)
This paper is a survey of recent empirical work on financial constraints faced by firms. It is organized as a series of stylized results which mirror what is generally understood about the severity of financial constraints and the effects that they have upon firms. The review of the literature shows that (a) financial constraints are a widespread key concern for firms, hindering their ability to carry out their optimal investment and growth trajectories and (b) the severity of such constraints depends on institutional and firm specific characteristics, as well as on the nature of investment projects.